2015
DOI: 10.15407/fz61.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Association of allelic polymorphisms of genes matrix Gla-protein system with ischemic atherothrombotic stroke

Abstract: Наведено результати визначення 10 поліморфізмів генів системи матриксного Gla-протеїну (ген MGP-T-138 →С (rs1800802), G-7 →A (rs1800801), Thr 83 →Ala (rs4236); ген VDR-FokI (rs2228570), BsmI (rs1544410), ApaI (rs7975232), TaqI (rs731236), ген GGCX-Arg 325 →Gln (rs699664), ген VKORС1-T 2255 →C (rs2359612), ген BMP-2-Ser 37 →Ala (rs2273073)) у 170 хворих з ішемічним атеротромботичним інсультом (ІАТІ) і 124 здорових індивідуумів (контрольна група). Встановлено, що існує зв'язок між ІАТІ і поліморфними варіантами … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Several observational studies have reported association of MGPG-7A polymorphism with VC and CVD: calcification in aorta and coronary arteries [115], atheromatic plaque and a nearly 4-fold risk for MI [110], ischemic atheroembolic stroke [121,122,123], and acute coronary episode [124,125]. In a cohort of 438 adults aged >60 years from the general population, G-7A polymorphism was an independent predictor of plasma dpucMGP levels.…”
Section: Mgp Gene Polymorphisms Vc Mortality and Cvdmentioning
confidence: 99%
“…Several observational studies have reported association of MGPG-7A polymorphism with VC and CVD: calcification in aorta and coronary arteries [115], atheromatic plaque and a nearly 4-fold risk for MI [110], ischemic atheroembolic stroke [121,122,123], and acute coronary episode [124,125]. In a cohort of 438 adults aged >60 years from the general population, G-7A polymorphism was an independent predictor of plasma dpucMGP levels.…”
Section: Mgp Gene Polymorphisms Vc Mortality and Cvdmentioning
confidence: 99%
“…Previously, we also investigated an association of VKORC1 T2255C polymorphism with IS in the same Ukrainian population [ 25 ]. It was shown that carriers of C/C genotype had a significant higher risk for IS than individuals with T/T genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Harbuzova et al analyzed the role of MGP in cerebrovascular disease. They found that the AA genotype of rs1800801 was associated with an increased risk of ischemic atherothrombotic stroke in Ukrainian females [18,19]. They also reported that the AA genotype associated with an altered prothrombin time, presumably causing increased hypercoagulability [20].…”
Section: Plos Onementioning
confidence: 99%